A composite diaphragm and its preparation method and application

By using composite separators in magnesium-sulfur batteries, the problem of rapid attenuation of battery capacity caused by polysulfide is solved, and the improvement of battery circulation performance and electrochemical performance is achieved.

CN119742534APending Publication Date: 2025-04-01INNER MONGOLIA WANHAO FLUOROCHEM +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411785238.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Magnesium-sulfur batteries have caused unstable electrode/electrolyte interface due to the polysulfide shuttle effect generated by sulfur electrodes during the reaction, resulting in poor battery circulation performance and rapid attenuation of capacity.

Method used

A composite separator is used, which is composed of a mixture of vinylidene fluoride copolymer and Cu-MOF-based phosphide/carbon material. By coating a modified layer on the substrate surface of the separator, a modified separator is formed to alleviate the dissolution and shuttle of the polysulfide.

Benefits of technology

It effectively alleviates the dissolution and shuttle of polysulfides during charging and discharging, and improves the electrochemical performance and cycle life of magnesium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742534A_ABST
    Figure CN119742534A_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of energy storage, and specifically relates to a composite diaphragm and its preparation method and application. The composite diaphragm includes a diaphragm substrate and a modified layer modified on the surface of the diaphragm substrate; the modified layer is composed of a mixture of a vinylidene fluoride copolymer and a Cu-MOF-based phosphide / carbon material. Compared with the prior art, the present invention solves the problem of rapid capacity decay in the prior art when polysulfides are dissolved in the electrolyte during the charge and discharge process. The present solution effectively alleviates the dissolution and shuttling of polysulfides, and improves the electrochemical performance of magnesium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy storage, and in particular relates to a composite diaphragm and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in consumer electronics, electric vehicles, and energy storage. As the demand for energy density increases, sulfur materials have a higher theoretical specific capacity (1675 mAh g -1 When paired with a lithium metal anode, the energy density of lithium-sulfur batteries can reach 2800Wh L -1 , and the energy density of magnesium-sulfur batteries is as high as 4000Wh L -1 In addition, since the reserves of magnesium metal in the earth's crust are more than 300 times that of lithium metal, magnesium-sulfur batteries are considered to be a rechargeable battery system with great application prospects.

[0003] Magnesium-sulfur batteries have received widespread attention as a low-cost, high-safety, and environmentally friendly secondary battery. However, due to the electronic insulation of elemental sulfur and the shuttling effect of polysulfides produced during the reaction of the sulfur electrode, the electrode / electrolyte interface is unstable, the battery cycle performance is poor, and the battery capacity decays rapidly. Summary of the invention

[0004] The purpose of the present invention is to provide a composite diaphragm and its preparation method and application in order to solve at least one of the above problems, so as to solve the problem of rapid capacity decay when polysulfides are dissolved in the electrolyte during the charging and discharging process in the prior art. The present solution effectively alleviates the dissolution and shuttling of polysulfides and improves the electrochemical performance of magnesium-sulfur batteries.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The first aspect of the present invention discloses a composite membrane, comprising a membrane substrate and a modified layer modified on the surface of the membrane substrate;

[0007] The modified layer is composed of a mixture of vinylidene fluoride copolymer and Cu-MOF-based phosphide / carbon material.

[0008] Preferably, the vinylidene fluoride copolymer is P(VDF-CTFE), the Cu-MOF-based phosphide / carbon material is Cu3P / C material, and the diaphragm substrate is a polyolefin film.

[0009] Preferably, the polyolefin film is a porous base film selected from one of a polyethylene film, a polypropylene film and a polyester nonwoven film.

[0010] Preferably, the thickness of the modified layer is 1 to 20 μm.

[0011] The second aspect of the present invention discloses a method for preparing the composite diaphragm as described above, comprising the following steps:

[0012] S1: adding deionized water and an emulsifier into a reaction kettle, raising the temperature, introducing the first monomer and the second monomer, raising the pressure, injecting a chain transfer agent and an initiator, and causing a copolymerization reaction; replenishing the initiator at regular intervals during the reaction; after the reaction is completed, washing and drying the reaction product to obtain a vinylidene fluoride copolymer;

[0013] S2: dissolving copper salt and trimesic acid in an alcohol solvent, preparing a Cu-MOF material by coprecipitation and calcining, and then adding phosphate and obtaining a Cu-MOF-based phosphide / carbon material by vapor deposition;

[0014] S3: adding the vinylidene fluoride copolymer obtained in step S1 and the Cu-MOF-based phosphide / carbon material obtained in step S2 into a solvent to prepare a slurry, and then coating it on the surface of the diaphragm substrate, and obtaining the composite diaphragm after drying.

[0015] Preferably, step S1 includes one or more of the following:

[0016] i) the first monomer is VDF, the second monomer is CTFE, and the molar ratio of the first monomer to the second monomer is 60-90:10-40;

[0017] ii) the chain transfer agent is one of dimethyl carbonate, diethyl carbonate and ethylene carbonate;

[0018] iii) the initiator is one or more of peroxysuccinic acid, dibenzoyl peroxide and tert-butyl perbenzoate;

[0019] iv) The reaction temperature of the copolymerization reaction is 55-75° C., the reaction pressure is 2.5-3.5 MPa, and the initiator is added every 20-40 minutes during the reaction; more preferably, the initiator is added every 35 minutes.

[0020] Preferably, step S2 includes one or more of the following:

[0021] i) the copper salt is one of copper chloride, copper nitrate and copper sulfate, and the mass ratio of the copper salt to trimesic acid is 1.2-2.0:0.5-0.9;

[0022] ii) the alcohol solvent is one or two of methanol, ethanol, n-propanol, isopropanol and n-butanol;

[0023] iii) the phosphate is one or two of potassium dihydrogen phosphate, sodium dihydrogen phosphate and diammonium hydrogen phosphate;

[0024] iv) the coprecipitation time is 2 to 5 hours;

[0025] v) the calcination temperature is 400-800° C.;

[0026] vi) The temperature of the vapor deposition is 250-400°C.

[0027] Preferably, step S3 includes one or more of the following:

[0028] i) the mass ratio of the vinylidene fluoride copolymer to the Cu-MOF-based phosphide / carbon material is 2.5:7.5;

[0029] ii) the solvent is one or more of dimethylformamide, dimethylacetamide and N-methyl-2-pyrrolidone;

[0030] iii) The drying is vacuum drying at a temperature of 40 to 60°C.

[0031] The third aspect of the present invention discloses an application of any of the above-mentioned composite diaphragms in the field of energy storage.

[0032] Preferably, the composite diaphragm is used as a battery diaphragm in a magnesium-sulfur battery.

[0033] The working principle of the present invention is:

[0034] By copolymerizing vinylidene fluoride (VDF) and chlorotrifluoroethylene (CTFE), the polar fluorine-containing functional groups in the copolymer have a high cohesive energy density, providing good mechanical strength for the composite membrane; and, by adding Cu-MOF-based phosphide / carbon materials to the modified layer, based on their adhesion, they can effectively alleviate the dissolution and shuttling of polysulfides, and ultimately improve the electrochemical performance of magnesium-sulfur batteries.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) In the present invention, the polar functional groups in the polymerizable fluorine-containing monomers are utilized to make the vinylidene fluoride copolymer have lower crystallinity and better thermal stability, thereby improving the film-forming property and flexibility of the composite diaphragm.

[0037] (2) The vinylidene fluoride copolymer and Cu-MOF-based phosphide / carbon composite material of the present invention are used as magnesium-sulfur battery separators, which effectively alleviate the capacity decay caused by polysulfides and greatly improve the cycle life of the battery, thereby improving the electrochemical performance of the magnesium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1The actual objects and SEM images of the polypropylene diaphragm (a) and the modified polypropylene diaphragm (b) in Example 2;

[0039] Figure 2 is the infrared spectrum of the vinylidene fluoride copolymer P (VDF-CTFE) in Example 2;

[0040] Figure 3 is the XRD pattern of the Cu-MOF-based phosphide / carbon material Cu3P / C in Example 2;

[0041] Figure 4 The cycle life diagram of the magnesium-sulfur battery equipped with the modified polypropylene separator prepared in Example 2 and Comparative Example 1 respectively. DETAILED DESCRIPTION

[0042] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0043] In the following description, unless otherwise specified, the reagents used are conventional commercially available products, and the methods used are well known in the art.

[0044] The present invention provides a composite diaphragm and a preparation method thereof, wherein the composite diaphragm is composed of a vinylidene fluoride copolymer and a metal phosphide / carbon material as a coating material to modify a diaphragm substrate, wherein the vinylidene fluoride copolymer is polymerized by a first monomer, vinylidene fluoride, and a second modified monomer, and the metal phosphide / carbon material is a copper-MOF-based phosphide / carbon material.

[0045] The specific preparation includes the following steps:

[0046] 1) Add deionized water and emulsifier to the reactor, stir evenly, raise the temperature to 55-75° C., increase the pressure to 2.5-3.5 MPa by adding VDF / CTFE mixed monomer, inject chain transfer agent and initiator, and start the reaction.

[0047] 2) During the reaction process, the pressure in the reactor is kept constant, and the initiator is added to the reactor every 20 to 40 minutes, for a total of 2 times. After the reaction is completed, the temperature is reduced and the pressure is released to recover the remaining gas. The material obtained by the reaction is washed and dried to obtain the vinylidene fluoride copolymer P (VDF-CTFE).

[0048] 3) Copper salt and trimesic acid are dissolved in an alcohol solvent to prepare a Cu-MOF material through co-precipitation, which is then calcined at high temperature and then phosphate is added to obtain a Cu3P / C material through vapor deposition.

[0049] 4) Add the above materials and P (VDF-CTFE) into a solvent in a certain ratio to prepare a slurry, coat the slurry on a diaphragm substrate (polyolefin film), and obtain a modified diaphragm after drying.

[0050] in:

[0051] The molar ratio of the first monomer VDF to the second monomer CTFE is 90:10 to 60:40. The chain transfer agent is one of dimethyl carbonate, diethyl carbonate, and ethylene carbonate, and the initiator is at least one of peroxysuccinic acid, dibenzoyl peroxide, and tert-butyl perbenzoate.

[0052] The copper salt is one of copper chloride, copper nitrate and copper sulfate, the alcohol solvent is one of methanol, ethanol, n-propanol, isopropanol and n-butanol or a mixture of two of them, the coprecipitation time is controlled within 2 to 5 hours, the high temperature calcination temperature is within 400 to 600° C., and the vapor deposition temperature is within 250 to 400° C.

[0053] The solvent for preparing the slurry is one of dimethylformamide, dimethylacetamide and N-methyl-2-pyrrolidone, and the polyolefin film is one of polyethylene film, polypropylene film and polyester non-woven fabric film.

[0054] The drying temperature of the separator after coating the slurry is 40°C to 60°C.

[0055] The composite diaphragm is used as a magnesium-sulfur battery diaphragm to alleviate the dissolution of polysulfides in the electrolyte during the charge and discharge process, thereby slowing down capacity decay, reducing self-discharge behavior, and reducing safety issues caused by thermal runaway. Specifically, the composite diaphragm can adsorb polysulfides in magnesium-sulfur batteries, effectively inhibit the shuttle effect, promote the reversibility of magnesium-sulfur batteries, and slow down the rapid decay of capacity.

[0056] Example 1

[0057] Composite diaphragm preparation:

[0058] 1) Add 5kg of deionized water and 4.5g of CF3CF2CF2O (CF(CF3)CF2O)CF(CF3)COONH4 to a 10L high-pressure polymerization reactor, stir, heat to 70°C, introduce VDF / CTFE mixed monomers into the reactor, and the pressure reaches 3.0MPa, with VDF accounting for 80% of the molar weight of the mixed monomers. Use a metering pump to pump 1.7g of ethylene carbonate and 5g of aqueous peroxide succinic acid solution into the reactor, start the reaction, and maintain a constant pressure. Add 1.5g of peroxide succinic acid every 35 minutes, twice in total; when the amount of the reaction mixed gas reaches the initial set value of 450g, the reaction ends, and the temperature is lowered and the pressure is released to recover the gas. The collected emulsion is demulsified and washed, and a white material is obtained after drying.

[0059] 2) 0.75 g of trimesic acid and 1.6 g of Cu(NO3)2·3H2O were dissolved in 40 mL of methanol, mixed and stirred for half an hour, left to stand for 2 hours, washed, filtered, recovered precipitates, and vacuum dried. After calcination at 500°C and phosphate (sodium dihydrogen phosphate) treatment at 300°C, Cu3P / C was obtained.

[0060] 3) Cu3P / C and P(VDF-CTFE) were added into 10 mL N-methyl-2-pyrrolidone solvent in a mass ratio of 7.5:2.5, mixed evenly, and the mixed slurry was applied onto a polypropylene diaphragm using a coating applicator, and vacuum dried to prepare a composite diaphragm.

[0061] Example 2

[0062] 1) Add 5kg of deionized water and 4.5g of CF3CF2CF2O (CF(CF3)CF2O)CF(CF3)COONH4 to a 10L high-pressure polymerization reactor, stir, heat to 70°C, and introduce VDF / CTFE mixed monomers into the reactor. The pressure reaches 3.0MPa, and VDF accounts for 90% of the molar weight of the mixed monomers. Use a metering pump to pump 1.7g of ethylene carbonate and 5g of aqueous peroxide succinic acid solution into the reactor respectively, start the reaction, and maintain a constant pressure. Add 1.5g of peroxide succinic acid every 35 minutes, for a total of 2 times; when the amount of the reaction mixed gas reaches the initial set value of 450g, the reaction ends, and the temperature is lowered and the pressure is released to recover the gas. The collected emulsion is demulsified and washed, and a white material is obtained after drying. The obtained white material is subjected to infrared testing by an infrared spectrometer, and the results are as follows Figure 2 shown.

[0063] 2) Dissolve 0.75g of trimesic acid and 1.6g of Cu(NO3)2·3H2O in 40mL of methanol, mix and stir evenly for half an hour, let stand for 2 hours, wash, filter and recover the precipitate, and vacuum dry. After calcination at 600℃ and phosphate treatment at 300℃, Cu3P / C is obtained. XRD test is performed on the obtained Cu3P / C, and the results are as follows: Figure 3 As shown, it indicates that Cu3P / C was successfully prepared.

[0064] 3) Cu3P / C and P(VDF-CTFE) were added into 10 mL N-methyl-2-pyrrolidone solvent in a mass ratio of 7.5:2.5, mixed evenly, and the mixed slurry was applied onto a polypropylene diaphragm using a coating applicator, and vacuum dried to prepare a composite diaphragm.

[0065] Figure 1 The composite membrane (b) prepared in this example and the actual object and SEM image of the polypropylene membrane substrate (a) before modification are shown. It can be seen that the membrane surface changes before and after modification.

[0066] Example 3

[0067] 1) Add 5kg of deionized water and 4.5g of CF3CF2CF2O (CF(CF3)CF2O)CF(CF3)COONH4 to a 10L high-pressure polymerization reactor, stir, heat to 70°C, introduce VDF / CTFE mixed monomers into the reactor, and the pressure reaches 3.0MPa, with VDF accounting for 70% of the molar weight of the mixed monomers. Use a metering pump to pump 1.7g of ethylene carbonate and 5g of aqueous peroxide succinic acid solution into the reactor, start the reaction, and maintain a constant pressure. Add 1.5g of peroxide succinic acid every 35 minutes, twice in total; when the amount of the reaction mixed gas reaches the initial set value of 450g, the reaction ends, and the temperature is lowered and the pressure is released to recover the gas. The collected emulsion is demulsified and washed, and a white material is obtained after drying.

[0068] 2) 0.75 g of trimesic acid and 1.6 g of Cu(NO3)2·3H2O were dissolved in 40 mL of methanol, mixed and stirred evenly for half an hour, left to stand for 2 hours, washed, filtered, recovered precipitates, and vacuum dried. After calcination at 700°C and phosphate treatment at 300°C, Cu3P / C was obtained.

[0069] 3) Cu3P / C and P(VDF-CTFE) were added into 10 mL N-methyl-2-pyrrolidone solvent in a mass ratio of 7.5:2.5, mixed evenly, and the mixed slurry was applied onto a polypropylene diaphragm using a coating applicator, and vacuum dried to prepare a composite diaphragm.

[0070] Example 4

[0071] 1) Add 5kg of deionized water and 4.5g of CF3CF2CF2O (CF(CF3)CF2O)CF(CF3)COONH4 to a 10L high-pressure polymerization reactor, stir, heat to 70°C, introduce VDF / CTFE mixed monomers into the reactor, and the pressure reaches 3.0MPa, with VDF accounting for 60% of the molar weight of the mixed monomers. Use a metering pump to pump 1.7g of ethylene carbonate and 5g of aqueous peroxide succinic acid solution into the reactor, start the reaction, and maintain a constant pressure. Add 1.5g of peroxide succinic acid every 35 minutes, twice in total; when the amount of the reaction mixed gas reaches the initial set value of 450g, the reaction ends, and the temperature is lowered and the pressure is released to recover the gas. The collected emulsion is demulsified and washed, and a white material is obtained after drying.

[0072] 2) 0.75 g of trimesic acid and 1.6 g of Cu(NO3)2·3H2O were dissolved in 40 mL of methanol, mixed and stirred for half an hour, left to stand for 2 hours, washed, filtered, recovered precipitates, and vacuum dried. After calcination at 800°C and phosphate treatment at 300°C, Cu3P / C was obtained.

[0073] 3) Cu3P / C and P(VDF-CTFE) were added into 10 mL N-methyl-2-pyrrolidone solvent in a mass ratio of 7.5:2.5, mixed evenly, and the mixed slurry was applied onto a polypropylene diaphragm using a coating applicator, and vacuum dried to prepare a composite diaphragm.

[0074] Comparative Example 1

[0075] 1) Add 5kg of deionized water and 4.5g of CF3CF2CF2O (CF (CF3) CF2O) CF (CF3) COONH4 to a 10L high-pressure polymerization reactor, stir, heat to 70°C, and introduce VDF monomer into the reactor to a pressure of 3.0MPa. Use a metering pump to pump 1.7g of ethylene carbonate and 5g of aqueous peroxide succinic acid solution into the reactor, start the reaction, and maintain a constant pressure. Add 1.5g of peroxide succinic acid every 35 minutes, twice in total; when the amount of the reaction mixed gas reaches the initial set value of 450g, the reaction ends, and the temperature is lowered and the pressure is released to recover the gas. The collected emulsion is demulsified and washed, and a white material is obtained after drying.

[0076] 2) 0.75 g of trimesic acid and 1.6 g of Cu(NO3)2·3H2O were dissolved in 40 mL of methanol, mixed and stirred for half an hour, left to stand for 2 hours, washed, filtered, recovered precipitates, and vacuum dried. After calcination at 800°C and phosphate treatment at 300°C, Cu3P / C was obtained.

[0077] 3) Cu3P / C and P(VDF-CTFE) were added into 10 mL N-methyl-2-pyrrolidone solvent in a mass ratio of 7.5:2.5, mixed evenly, and the mixed slurry was applied onto a polypropylene diaphragm using a coating applicator, and vacuum dried to prepare a composite diaphragm.

[0078] The composite membranes prepared in Example 2 and Comparative Example 1 were respectively assembled in magnesium-sulfur batteries and tested at room temperature at a current of 0.1C (1C = 1673 mAg -1 ) to conduct cycle life test, the results are as follows Figure 4 As shown, it can be seen that the polypropylene diaphragm modified by Example 2 of the present scheme still has a high specific capacity and stable coulombic efficiency after 100 cycles and can slow down overcharging. In contrast, the capacity of the diaphragm of Comparative Example 1 decays faster as the number of cycles increases, and the coulombic efficiency shows that there is still an overcharge phenomenon, indicating that the modification of the polypropylene diaphragm in this scheme can ensure that the performance decay of the magnesium-sulfur battery is small at a longer cycle time.

[0079] In summary, the test results show that the composite diaphragm prepared by the present invention not only has good mechanical strength and flexibility, but also uses it as a diaphragm for magnesium-sulfur batteries to slow down the shuttling and dissolution of polysulfides, thereby improving the battery cycle performance.

[0080] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A composite diaphragm, characterized in that: It includes a membrane substrate and a modified layer modified on the surface of the membrane substrate; The modified layer is composed of a mixture of vinylidene fluoride copolymer and Cu-MOF-based phosphide / carbon material.

2. A composite diaphragm according to claim 1, characterized in that: The vinylidene fluoride copolymer is P (VDF-CTFE), the Cu-MOF-based phosphide / carbon material is Cu3P / C material, and the diaphragm substrate is a polyolefin film.

3. A composite diaphragm according to claim 2, characterized in that: The polyolefin film is a porous base film selected from one of polyethylene film, polypropylene film and polyester non-woven fabric film.

4. A composite diaphragm according to claim 1, characterized in that: The thickness of the modified layer is 1 to 20 μm.

5. A method for preparing a composite diaphragm according to any one of claims 1 to 4, characterized in that: The steps include: S1: adding deionized water and an emulsifier into a reaction kettle, raising the temperature, introducing the first monomer and the second monomer, raising the pressure, injecting a chain transfer agent and an initiator, and causing a copolymerization reaction; replenishing the initiator at regular intervals during the reaction; after the reaction is completed, washing and drying the reaction product to obtain a vinylidene fluoride copolymer; S2: dissolving copper salt and trimesic acid in an alcohol solvent, preparing a Cu-MOF material by coprecipitation and calcining, and then adding phosphate and obtaining a Cu-MOF-based phosphide / carbon material by vapor deposition; S3: adding the vinylidene fluoride copolymer obtained in step S1 and the Cu-MOF-based phosphide / carbon material obtained in step S2 into a solvent to prepare a slurry, and then coating it on the surface of the diaphragm substrate, and obtaining the composite diaphragm after drying.

6. The method for preparing a composite diaphragm according to claim 5, characterized in that: Step S1 includes one or more of the following: i) the first monomer is VDF, the second monomer is CTFE, and the molar ratio of the first monomer to the second monomer is 60-90:10-40; ii) the chain transfer agent is one of dimethyl carbonate, diethyl carbonate and ethylene carbonate; iii) the initiator is one or more of peroxysuccinic acid, dibenzoyl peroxide and tert-butyl perbenzoate; iv) The reaction temperature of the copolymerization reaction is 55-75° C., the reaction pressure is 2.5-3.5 MPa, and the initiator is added every 20-40 minutes during the reaction.

7. The method for preparing a composite diaphragm according to claim 5, characterized in that: Step S2 includes one or more of the following: i) the copper salt is one of copper chloride, copper nitrate and copper sulfate, and the mass ratio of the copper salt to trimesic acid is 1.2-2.0:0.5-0.9; ii) the alcohol solvent is one or two of methanol, ethanol, n-propanol, isopropanol and n-butanol; iii) the phosphate is one or two of potassium dihydrogen phosphate, sodium dihydrogen phosphate and diammonium hydrogen phosphate; iv) the coprecipitation time is 2 to 5 hours; v) the calcination temperature is 400-800° C.; vi) The temperature of the vapor deposition is 250-400°C.

8. The method for preparing a composite diaphragm according to claim 5, characterized in that: Step S3 includes one or more of the following: i) the mass ratio of the vinylidene fluoride copolymer to the Cu-MOF-based phosphide / carbon material is 2.5:7.5; ii) the solvent is one or more of dimethylformamide, dimethylacetamide and N-methyl-2-pyrrolidone; iii) The drying is vacuum drying at a temperature of 40 to 60°C.

9. Use of the composite diaphragm according to any one of claims 1 to 4 in the field of energy storage.

10. The use according to claim 9, characterized in that: The composite diaphragm is used as a battery diaphragm in magnesium-sulfur batteries.